THE ROLE OF MODERN COMPUTER TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF GASTROINTESTINAL DISEASES - Atakhanov Sanjarbek Anvarovich; Jamoldinov Saydillo Xasanovich; Rahmonova Gulzodaxon Sherali qizi (Bright Mind Publishing, 2025)
This article highlights the role of modern computer technologies in the diagnosis and treatment of gastrointestinal diseases. With the help of artificial intelligence, computed tomography, endoscopic systems and data processing programs used in medicine, the possibilities for early detection of diseases, correct diagnosis and selection of individual treatment methods are expanding. Also, ways of monitoring and effective control of the patient's condition through analytical platforms and digital monitoring systems are considered. The study analyzes the role of innovative technologies in combating gastrointestinal diseases based on statistical data and identifies promising areas.
Keywords: Gastrointestinal diseases, computer technologies, artificial intelligence, diagnostic systems, endoscopy, digital medicine, diagnosis, medical information systems